Application of Motif Creation with Techniques Pounding Ecoprint Using Sidamanik Tea Leaves as a Natural Dye - Kumalasari, Desi; Surani, Surani (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This research aims to identify and analyze the effectiveness of motif creation using the pounding ecoprint technique with Sidamanik tea leaves as a natural dye, and to determine the factors influencing the final ecoprint results. The research method employed was experimental, with data collected through questionnaires distributed to 20 panelists and observations by 2 observers. The findings indicate that motif sharpness and color fastness varied significantly depending on the fabric type and mordant combination used. For motif sharpness, ecoprint on canvas fabric with a mixture of tunjung, soda ash, and alum mordants achieved the highest score (90%), while rayon fabric with tunjung, soda ash, and alum mordants showed the lowest score (61%). Regarding color fastness, the most significant color change occurred in samples with tunjung pre-mordant and alum post-mordant. Canvas fabric with tunjung mordant demonstrated the best color fastness (72%), whereas rayon fabric with tunjung mordant had the lowest color fastness (42%). Overall, this study suggests the potential of Sidamanik tea leaves as a natural dye in ecoprint, with the appropriate selection of fabric type and mordant being crucial for optimal results.